A low-temperature stress-relief annealing method for SLM-formed copper components

CN123000016APending Publication Date: 2026-10-30宁波众远新材料科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611356077.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0009]本发明针对现有技术中SLM成型铜构件去应力退火过程中高温退火导致导电性能衰减、低温时效去应力效果差的技术矛盾,提供一种低温保导电去应力退火方法

Benefits of technology

本发明通过阶梯升温和阶梯冷却方式,有效避免了热处理过程中的温差应力和热变形。经本发明工艺处理后的铜构件尺寸变形量可控制在0.1%以内(纯铜构件0.08%、CuCrZr构件0.09%、CuSn构件0.07%),远优于高温退火工艺(0.6%以上)。同时,全程氩气保护气氛有效防止了构件氧化,构件表面光洁无氧化。上述优势大幅降低了后续加工成本和生产周期,提升了产品的市场竞争力和经济效益。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123000016A_ABST
    Figure CN123000016A_ABST
Patent Text Reader

Abstract

The application discloses a low-temperature stress relief annealing method for SLM formed copper components, and belongs to the technical field of post-processing of metal additive manufacturing. The application provides a low-temperature annealing process combining stepwise heating and stepwise cooling, aiming at the technical contradiction that high-temperature annealing in the stress relief annealing process of a selective laser melting (SLM) formed copper component leads to the attenuation of the electric conductivity and the poor stress relief effect of low-temperature aging. The application realizes the effective release of residual stress by dislocation movement and grain boundary migration in the 400-450 DEG C low-temperature range, avoids the coarsening of the strengthening phase, and achieves the excellent effects that the residual stress is less than or equal to 100 MPa, the electric conductivity is kept above 73% IACS, and the size deformation amount is less than or equal to 0.1%, which is suitable for pure copper, CuCrZr, CuSn and other copper alloy components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal additive manufacturing post-processing technology, and more specifically to a low-temperature conductive stress-relieving annealing method for SLM-formed copper components. Background Technology

[0002] Selective laser melting (SLM), as one of the core technologies of metal additive manufacturing, is widely used in the precision forming of copper components due to its advantages such as high forming accuracy and customizable complex structures. Copper and copper alloys have excellent electrical and thermal conductivity, making them key materials in fields such as power, electronics, and aerospace. SLM technology can manufacture complex copper components that are difficult to form using traditional processing methods, significantly improving the design freedom and production efficiency of components, and has broad application prospects in high-end application areas such as electrical connectors, heat dissipation devices, and high-frequency electronic packaging.

[0003] However, there is an inherent technical challenge in the SLM forming process: the laser beam rapidly melts and solidifies metal powder with extremely high energy density, and the cooling rate of the molten pool can reach 10. 5 ~10 6 The extremely rapid heating and cooling rate (℃ / s) results in a significant temperature gradient between the molten pool and the solidified region, leading to substantial residual stress within the copper component. This residual stress can cause warping, deformation, and cracking, severely impacting the component's dimensional accuracy, mechanical properties, and service reliability. Therefore, annealing is essential for stress-relieving SLM-formed copper components to eliminate internal residual stress and ensure dimensional stability and operational reliability.

[0004] Meanwhile, the core applications of copper components demand extremely high conductivity. Applications such as electrical conductive components and high-frequency electronic components require copper components to maintain the highest possible conductivity; any degradation in conductivity directly affects the component's performance and lifespan. Therefore, maximizing the preservation of conductivity while eliminating residual stress has become a critical issue that the post-processing technology for SLM-formed copper components urgently needs to address.

[0005] Currently, the existing technologies for stress-relief annealing processes for SLM-formed copper components are mainly divided into two categories: high-temperature stress-relief annealing process and conventional low-temperature aging process. However, both have obvious defects and shortcomings and cannot meet the dual requirements of "low-temperature stress relief + electrical conductivity preservation".

[0006] Disadvantages of High-Temperature Stress-Relief Annealing: While high-temperature annealing can effectively eliminate residual stress, it also brings serious negative effects. For copper alloys, at high temperatures, room-temperature strengthening phases (such as Cr and Zr precipitates in CuCrZr) coarsen and aggregate, disrupting the metastable supersaturated solid solution structure of the alloy. This leads to a significant decrease in the electrical conductivity of copper components, failing to meet the requirements for conductive parts. Furthermore, high-temperature annealing also causes significant thermal deformation in copper components, reducing dimensional accuracy and increasing subsequent processing costs.

[0007] The drawbacks of conventional low-temperature aging treatment: While low-temperature aging treatment can preserve the electrical conductivity of copper alloys relatively well, the excessively low heat treatment temperature restricts dislocation movement and grain boundary migration within the copper components, preventing the effective release of residual stress. This falls far short of meeting the requirements for dimensional stability and crack resistance during component service. In summary, existing stress-relief annealing processes face a dilemma: if the annealing temperature is too high, the electrical conductivity will significantly decrease; if the annealing temperature is too low, the residual stress will not be fully released.

[0008] Therefore, how to effectively eliminate residual stress in SLM-formed copper components while maximizing their electrical conductivity is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0009] This invention addresses the technical contradiction in existing SLM-formed copper component stress-relief annealing processes, where high-temperature annealing leads to decreased conductivity and low-temperature aging results in poor stress relief. It provides a low-temperature conductivity-preserving stress-relief annealing method. This invention aims to achieve the dual effect of "low-temperature stress relief + conductivity preservation" by precisely controlling the annealing temperature range, holding time, heating rate, cooling method, and heat treatment atmosphere, while simultaneously ensuring the dimensional accuracy and mechanical properties of the component. Utilizing the dislocation movement and grain boundary migration patterns of copper alloys within the low-temperature range (400-450℃), residual stress is effectively released without inducing coarsening of strengthening phases or disrupting the metastable solid solution structure. Simultaneously, controlling the heating rate, cooling method, and heat treatment atmosphere prevents thermal deformation and oxidation of the component, further guaranteeing conductivity and dimensional accuracy.

[0010] To achieve the above objectives, the present invention adopts the following technical solution: The first objective of this invention is to provide a low-temperature annealing method for maintaining electrical conductivity and relieving stress in SLM-formed copper components, comprising the following steps: (1) Pretreatment: Clean the surface of the copper components after SLM forming to remove unmelted powder and oil stains on the surface of the components; avoid impurities affecting the surface quality and internal structure of the components during the annealing process.

[0011] (2) Loading and atmosphere conditioning: Place the pretreated copper components into the vacuum annealing furnace, arrange the components properly to avoid contact between the components, which may cause adhesion or deformation during the annealing process. After vacuuming, introduce protective gas to keep the furnace in a protective gas atmosphere to prevent air from entering the furnace and causing oxidation of the components, and to avoid the oxide layer affecting the conductivity.

[0012] (3) Step heating: The annealing furnace is heated in a step heating manner to avoid the thermal stress caused by rapid heating. The specific heating regime is as follows: First stage: heat from room temperature to 200℃, with the heating rate controlled at 5-8℃ / min. After reaching 200℃, hold for 30-40min. The main purpose of this stage is to preheat the components to make the internal temperature of the components uniform and avoid local temperature differences during the subsequent heating process. Second stage: heat from 200℃ to the target temperature, with the heating rate controlled at 3-5℃ / min. (4) Low temperature heat preservation and stress relief: After the component is heated to the target temperature, it is kept for 1.5 to 3 hours. During the heat preservation process, the temperature fluctuation range in the furnace is controlled within ±5℃. Ensure that the component is heated evenly and ensure the consistency of stress relief effect. Low temperature heat preservation can cause dislocations inside the component to slip, climb, and grain boundaries to migrate, thereby effectively releasing the residual stress generated in the SLM forming process, while avoiding the coarsening of the strengthening phase and retaining the electrical conductivity. (5) Step-cooling: After the heat preservation is completed, a step-cooling method is adopted to avoid the rapid cooling that causes residual stress to be generated in the component again. The specific cooling system is as follows: First stage: cool from the target temperature to 200℃, and the cooling rate is controlled at 2 to 4℃ / min; the cooling is slow in this stage, so that the internal temperature of the component drops evenly and the thermal stress is reduced; Second stage: cool from 200℃ to room temperature, turn off the heating device, and let the component cool naturally with the furnace; maintain the protective gas atmosphere in the furnace during the above two stages of cooling; until the component temperature drops to room temperature, to avoid the component from contacting the air and oxidizing during the cooling process.

[0013] (6) Post-processing: After the component is cooled to room temperature, the component is taken out and the surface is cleaned to complete the annealing method.

[0014] As a preferred technical solution, the surface cleaning method in step (1) is as follows: the surface of the component is purged with high-pressure argon gas at a pressure of 0.3 to 0.5 MPa, and ultrasonically cleaned with anhydrous ethanol for 10 to 15 minutes. After cleaning, it is dried at 80 to 100°C for 20 to 30 minutes, and argon gas is continuously introduced during the drying process.

[0015] As a preferred technical solution, in step (2), the vacuum level inside the furnace is evacuated to 5×10⁻⁶. -3Below Pa, the protective gas is high-purity argon with a purity ≥99.99%; the furnace atmosphere is replaced with an argon atmosphere, the argon flow rate is controlled at 5-10 L / min, and the furnace pressure is maintained at a slightly positive pressure of 0.01-0.02 MPa.

[0016] As a preferred technical solution, the copper components in step (2) are kept at a distance of 10-20 mm from the furnace wall and the furnace bottom plate to ensure uniform heating.

[0017] As a preferred technical solution, the target temperature in step (3) is determined according to the alloy type of the copper component: the target temperature for pure copper components is 400-420℃, the target temperature for CuCrZr copper alloy components is 420-440℃, and the target temperature for CuSn copper alloy components is 430-450℃; different alloys adopt different suitable target temperatures, which can further improve the stress relief effect and the retention effect of electrical conductivity.

[0018] As a preferred technical solution, the protective gas in step (5) is high-purity argon gas with a purity ≥ 99.99%.

[0019] As a preferred technical solution, the post-processing in step (6) is as follows: the surface of the component is purged with high-pressure argon gas at a pressure of 0.2-0.6MPa to remove residual impurities; for components with high surface precision requirements and an average roughness Ra of 0.8-2.5μm, post-processing can be carried out by sandblasting, mechanical grinding and polishing, electrolytic polishing or abrasive flow polishing.

[0020] As a preferred technical solution, the SLM-formed copper component is a pure copper component, a CuCrZr copper alloy component, or a CuSn copper alloy component.

[0021] Another object of this application is to provide the application of the above-described annealing method in relieving stress in SLM-molded copper components and / or maintaining the electrical conductivity of SLM-molded copper components.

[0022] As can be seen from the above technical solution, the core advantage of this invention compared with the prior art is as follows: (1) It achieves the dual effects of "low-temperature stress relief + electrical conductivity preservation", with significant performance advantages. This invention achieves effective stress release by precisely controlling the annealing temperature within the low-temperature range of 400–450°C, utilizing the principles of dislocation movement and grain boundary migration in copper alloys within this temperature range, without inducing coarsening of strengthening phases or disrupting the metastable solid solution structure. SLM-formed copper components treated with this invention exhibit residual stress reduced to below 100 MPa (85 MPa for pure copper components, 85 MPa for CuCrZr components, and 98 MPa for CuSn components), while maintaining excellent conductivity (100% IACS for pure copper components, 92% IACS for CuCrZr components, and 73% IACS for CuSn components). Compared to existing high-temperature annealing processes (which offer good stress relief but significantly reduce conductivity) and conventional low-temperature aging processes (which maintain good conductivity but offer poor stress relief), this invention achieves a balance between stress relief and conductivity for the first time, solving a long-standing technical problem in this field.

[0023] (2) It is compatible with a variety of copper alloys and has strong versatility. This invention sets appropriate target temperature ranges for different copper alloys (pure copper, CuCrZr, CuSn, etc.), enabling precise control based on alloy composition and strengthening phase characteristics, thus possessing wide applicability. This invention is not only applicable to pure copper components, but also to precipitation-strengthened copper alloys (such as CuCrZr) and solid solution-strengthened copper alloys (such as CuSn), meeting the post-processing requirements of copper components in different application scenarios.

[0024] (3) Avoid heat deformation and oxidation, and reduce subsequent processing costs. This invention effectively avoids thermal stress and thermal deformation during heat treatment by using a stepped heating and cooling method. The dimensional deformation of copper components processed by this invention can be controlled within 0.1% (0.08% for pure copper components, 0.09% for CuCrZr components, and 0.07% for CuSn components), far superior to high-temperature annealing (above 0.6%). Simultaneously, the argon protective atmosphere throughout the process effectively prevents component oxidation, resulting in a smooth, oxidation-free surface. These advantages significantly reduce subsequent processing costs and production cycles, enhancing the product's market competitiveness and economic benefits. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the low-temperature conductive stress-relieving annealing method for SLM-formed copper components according to the present invention.

[0027] Figure 2 The bar chart shows the comparison of residual stress and conductivity of CuCrZr copper alloy components after treatment with the process of this invention, the existing high-temperature stress-relief annealing process, and the existing conventional low-temperature aging process. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1

[0030] A low-temperature annealing method for maintaining electrical conductivity and relieving stress in SLM-formed copper components (pure copper components). According to the process steps of the present invention (such as...) Figure 1 Annealing is performed on pure copper components formed by SLM.

[0031] (1) Pretreatment: The surface of the component was purged with 0.4MPa high-pressure argon gas to remove unmelted powder; then it was ultrasonically cleaned with anhydrous ethanol for 12 minutes to remove oil and fine dust; the component was placed in a drying oven and dried at 80℃ for 25 minutes. Argon gas was continuously introduced during the drying process to ensure that there was no moisture residue on the surface of the component.

[0032] (2) Loading and Atmosphere Conditioning: Place the dried pure copper components into the vacuum annealing furnace, maintaining a 15mm gap between the components and the furnace walls and bottom plate to ensure uniform heating. After closing the furnace door, evacuate to 3×10⁻⁶. -3 Pa, then high-purity argon gas (99.99% purity) is introduced at a flow rate of 8 L / min, and the pressure inside the furnace is maintained at a slightly positive pressure of 0.015 MPa.

[0033] (3) Step heating: Heat from room temperature to 200℃ at a rate of 6℃ / min and hold for 35min; then heat from 200℃ to 410℃ (target temperature for pure copper) at a rate of 4℃ / min.

[0034] (4) Low temperature heat preservation and stress relief: heat preservation at 410℃ for 2 hours, and the temperature fluctuation inside the furnace is controlled within ±5℃.

[0035] (5) Step cooling: Cool from 410°C to 200°C at a rate of 3°C / min; then turn off the heating device and let the furnace cool naturally to room temperature, maintaining an argon atmosphere in the furnace during the cooling process.

[0036] (6) Post-treatment: After the component is cooled to room temperature, the surface of the component is purged with 0.4MPa high-pressure argon gas to complete the annealing.

[0037] Test results: The residual stress of the pure copper component was 85 MPa; the conductivity was 100% IACS; the dimensional deformation was 0.08%; and the surface was smooth and free of oxidation.

[0038] Example 2

[0039] A low-temperature annealing method for maintaining electrical conductivity and relieving stress in SLM-formed copper components (CuCrZr copper alloy components). According to the process steps of this invention, the CuCrZr copper alloy component formed by SLM is annealed.

[0040] (1) Pretreatment: The surface of the component was purged with 0.5MPa high-pressure argon gas to remove unmelted powder; then it was ultrasonically cleaned with anhydrous ethanol for 15min to remove oil and fine dust; the component was placed in a drying oven and dried at 90℃ for 20min, with argon gas continuously introduced during the drying process.

[0041] (2) Loading and Atmosphere Conditioning: Place the dried CuCrZr copper alloy components into the vacuum annealing furnace, maintaining a 15mm gap between the components and the furnace wall and bottom plate. After closing the furnace door, evacuate to 4×10⁻⁶. -3 Pa, then high-purity argon gas (99.99% purity) is introduced at a flow rate of 10 L / min, and the pressure inside the furnace is maintained at 0.02 MPa.

[0042] (3) Step heating: Heat from room temperature to 200℃ at a rate of 8℃ / min and hold for 30min; then heat from 200℃ to 430℃ (target temperature of CuCrZr) at a rate of 5℃ / min.

[0043] (4) Low temperature heat preservation and stress relief: heat preservation at 430℃ for 2.5h, and the temperature fluctuation inside the furnace is controlled within ±5℃.

[0044] (5) Step cooling: Cool from 430°C to 200°C at a rate of 4°C / min; then turn off the heating device and let the furnace cool naturally to room temperature, maintaining an argon atmosphere in the furnace during the cooling process.

[0045] (6) Post-treatment: After the component is cooled to room temperature, the surface of the component is purged with 0.5MPa high-pressure argon gas to complete the annealing.

[0046] Test results: The residual stress of the CuCrZr copper alloy component was 85 MPa; the conductivity was 92% IACS; the dimensional deformation was 0.09%; and the surface was smooth and free of oxidation.

[0047] Example 3

[0048] A low-temperature annealing method for maintaining electrical conductivity and relieving stress in SLM-formed copper components (CuSn copper alloy components). According to the process steps of the present invention, the CuSn copper alloy component formed by SLM is subjected to annealing treatment.

[0049] (1) Pretreatment: The surface of the component was purged with 0.3MPa high-pressure argon gas to remove unmelted powder; then it was ultrasonically cleaned with anhydrous ethanol for 10 min to remove oil and fine dust; the component was placed in a drying oven and dried at 100℃ for 30 min, with argon gas continuously introduced during the drying process.

[0050] (2) Loading and Atmosphere Conditioning: Place the dried CuSn copper alloy components into the vacuum annealing furnace, maintaining a 15mm gap between the components and the furnace wall and bottom plate. After closing the furnace door, evacuate to 5×10⁻⁶. -3 Pa, then high-purity argon gas (99.99% purity) is introduced at a flow rate of 5 L / min, and the pressure inside the furnace is maintained at 0.01 MPa.

[0051] (3) Step heating: Heat from room temperature to 200℃ at a rate of 5℃ / min and hold for 40min; then heat from 200℃ to 440℃ (target temperature of CuSn) at a rate of 3℃ / min.

[0052] (4) Low temperature heat preservation and stress relief: heat preservation at 440℃ for 2.5h, and the temperature fluctuation inside the furnace is controlled within ±5℃.

[0053] (5) Step cooling: Cool from 440°C to 200°C at a rate of 2°C / min; then turn off the heating device and let the furnace cool naturally to room temperature, maintaining an argon atmosphere in the furnace during the cooling process.

[0054] (6) Post-treatment: After the component is cooled to room temperature, the surface of the component is purged with 0.3MPa high-pressure argon gas to complete the annealing.

[0055] Test results: The residual stress of the CuSn copper alloy component was 98 MPa; the conductivity was 73% IACS; the dimensional deformation was 0.07%; and the surface was smooth and free of oxidation.

[0056] Comparative Example 1 Pure Cu components (200℃ insulation is omitted, and the temperature is directly increased to the target temperature). This comparative example is used to verify the necessity of the first stage of the 200℃ heat preservation step in the stepped heating process.

[0057] The remaining parameters are the same as in Example 1, except that the operation of "heating from room temperature to 200°C at a rate of 6°C / min and holding for 35 min" is omitted, and the temperature is directly increased to 410°C at a rate of 4°C / min.

[0058] Test results: The residual stress of the component is 114 MPa; the conductivity is 99.8% IACS; and the dimensional deformation is 0.12%.

[0059] Analysis: Eliminating the 200℃ insulation and directly raising the temperature resulted in an increased temperature difference between the inside and outside of the component, generating additional thermal stress. This increased the residual stress to 114 MPa (compared to 85 MPa in Example 1) and the dimensional deformation to 0.12% (compared to 0.08% in Example 1). This indicates that the intermediate insulation step plays a crucial role in ensuring uniform component temperature and avoiding the introduction of additional thermal stress.

[0060] Comparative Example 2 High-temperature stress-relief annealing of CuCrZr (existing technology) This comparative example is used to compare the differences in technical effects between the present invention and existing high-temperature stress-relief annealing methods.

[0061] The CuCrZr copper alloy components were treated using the high-temperature stress-relief annealing process in the prior art. The specific parameters were as follows: steps (3), (4), and (5) of Example 2 were replaced with "heating from room temperature to 600°C at a rate of 10°C / min, holding for 2 hours, and then cooling to room temperature in the furnace". The remaining steps (1), (2), and (6) were the same as in Example 2.

[0062] Test results: The residual stress of the component is 75 MPa; however, the conductivity is only 70% IACS; and the dimensional deformation is 0.6%.

[0063] Analysis: For example Figure 2 As shown, although high-temperature annealing has a better stress-relieving effect (residual stress 75 MPa, lower than 92 MPa in Example 2), the trade-off is a significant decrease in conductivity to 70% IACS (compared to 85% IACS in Example 2), and a high dimensional deformation of 0.6% (compared to 0.09% in Example 2). This indicates that while high-temperature annealing can effectively eliminate residual stress, it severely sacrifices the conductivity and dimensional accuracy of the copper alloy, failing to meet the requirements for conductive components.

[0064] Comparative Example 3 Conventional low-temperature aging of CuCrZr (existing technology) This comparative example is used to compare the differences in technical effects between the present invention and existing conventional low-temperature aging methods.

[0065] The CuCrZr copper alloy components were treated using the conventional low-temperature aging process in the prior art. The specific parameters were as follows: steps (3), (4), and (5) of Example 2 were replaced with "heating from room temperature to 380°C at a rate of 10°C / min, holding for 2 hours, and then cooling to room temperature in the furnace". The remaining steps (1), (2), and (6) were the same as in Example 2.

[0066] Test results: The conductivity of the component is 80% IACS, but the residual stress is 150 MPa; the dimensional deformation is 0.06%.

[0067] Analysis: For example Figure 2 As shown, although the conductivity remained good (80% IACS, close to 85% IACS in Example 2) and the dimensional deformation was small (0.06%), the residual stress was as high as 150 MPa (92 MPa in Example 2), which is far from meeting the stress relief requirements. This indicates that the temperature of 380°C is too low, which restricts dislocation movement and grain boundary migration, and the residual stress cannot be effectively released.

[0068] Comparative Example 4 CuSn components (eliminating stepped controlled cooling, direct furnace cooling) This comparative example is used to verify the necessity of the first-stage controlled cooling step in stepped cooling.

[0069] The remaining parameters are the same as in Example 3, except that after the 440℃ heat preservation is completed, the cooling rate of 2℃ / min is not controlled, and the furnace is cooled directly.

[0070] Test results: The residual stress of the component is 109 MPa; the conductivity is 72.5% IACS; and the dimensional deformation is 0.1%.

[0071] Analysis: Although the average cooling rate of furnace cooling is slower when step-controlled cooling is eliminated and the components are cooled directly with the furnace, the non-uniformity of the temperature field inside the furnace still reintroduces some residual thermal stress during the cooling process, causing the residual stress to rise to 109 MPa (98 MPa in Example 3). This shows that step-controlled cooling plays an important role in avoiding the reintroduction of residual stress during the cooling process.

[0072] The low-temperature conductive stress-relieving annealing method for SLM-formed copper components provided by this invention can be widely applied to the post-processing of SLM-formed copper and copper alloy components in fields such as power conductive components, high-frequency electronic components, and aerospace copper components. This invention features simple operation, low equipment requirements, and wide applicability, demonstrating promising industrial application prospects and economic benefits. Copper components processed using this invention retain the high-precision, complex structural advantages of SLM forming while eliminating internal residual stress, and simultaneously preserving excellent conductivity. This meets the stringent requirements of high-end applications for dimensional stability, reliability, and conductivity of copper components.

[0073] The various embodiments in the specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0074] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A low-temperature annealing method for maintaining electrical conductivity and relieving stress in SLM-formed copper components, characterized in that, Includes the following steps: (1) Pretreatment: Clean the surface of the copper components after SLM forming to remove unmelted powder and oil stains from the surface of the components; (2) Loading and atmosphere conditioning: Place the pretreated copper components into the vacuum annealing furnace, evacuate the furnace and introduce protective gas to make the furnace atmosphere protective. (3) Step heating: The annealing furnace is heated by step heating. The first stage: the temperature is raised from room temperature to 200℃, and the heating rate is controlled at 5-8℃ / min. After reaching 200℃, the temperature is held for 30-40min. The second stage: the temperature is raised from 200℃ to the target temperature, and the heating rate is controlled at 3-5℃ / min. (4) Low temperature heat preservation and stress relief: After the component is heated to the target temperature, it is kept for 1.5 to 3 hours. During the heat preservation process, the temperature fluctuation range inside the furnace is controlled to be ±5℃. (5) Step cooling: After the heat preservation is completed, the step cooling method is adopted for cooling. The first stage: cooling from the target temperature to 200℃, the cooling rate is controlled at 2~4℃ / min; the second stage: cooling from 200℃ to room temperature, the heating device is turned off, and the components are allowed to cool naturally with the furnace; the protective gas atmosphere in the furnace is maintained during the above two stages of cooling. (6) Post-processing: After the component cools to room temperature, remove the component and clean the surface to complete the annealing process.

2. The annealing method according to claim 1, characterized in that, The surface cleaning method described in step (1) is as follows: the surface of the component is purged with high-pressure argon gas at a pressure of 0.3 to 0.5 MPa, and ultrasonically cleaned with anhydrous ethanol for 10 to 15 minutes. After cleaning, it is dried at 80 to 100°C for 20 to 30 minutes, and argon gas is continuously introduced during the drying process.

3. The annealing method according to claim 1, characterized in that, In step (2), the vacuum level inside the furnace is evacuated to 5×10⁻⁶. -3 Below Pa, the protective gas is high-purity argon with a purity ≥99.99%; the furnace atmosphere is replaced with an argon atmosphere, the argon flow rate is controlled at 5-10 L / min, and the furnace pressure is maintained at a slightly positive pressure of 0.01-0.02 MPa.

4. The annealing method according to claim 1, characterized in that, In step (2), the copper components are kept at a distance of 10-20 mm from the furnace wall and the furnace bottom plate.

5. The annealing method according to claim 1, characterized in that, The target temperature mentioned in step (3) is determined according to the alloy type of the copper component: the target temperature for pure copper components is 400-420℃, the target temperature for CuCrZr copper alloy components is 420-440℃, and the target temperature for CuSn copper alloy components is 430-450℃.

6. The annealing method according to claim 1, characterized in that, The protective gas mentioned in step (5) is high-purity argon with a purity ≥ 99.99%.

7. The annealing method according to claim 1, characterized in that, The post-processing described in step (6) is as follows: the surface of the component is purged with high-pressure argon gas at a pressure of 0.2-0.6MPa to remove residual impurities; for components with high surface precision requirements and an average roughness Ra of 0.8-2.5μm, post-processing can be carried out by sandblasting, mechanical grinding and polishing, electrolytic polishing or abrasive flow polishing.

8. The annealing method according to claim 1, characterized in that, The SLM-formed copper component is a pure copper component, a CuCrZr copper alloy component, or a CuSn copper alloy component.

9. The application of the annealing method according to any one of claims 1-8 in relieving stress in SLM-molded copper components and / or maintaining the electrical conductivity of SLM-molded copper components.